Pengaruh Kompensasi, Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Driver Gojek - Nariswari, Adinda Ragil; Silalahi, Edward Efendi; Hasanuddin Hasanuddin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Online transportation services such as Gojek provide ease of mobility for the community. However, driver performance still faces various problems, especially related to attitude, communication, and consistency in accepting orders. Based on the results of a pre-survey, the majority of respondents stated that they were less motivated because the bonuses and incentives received were not commensurate with the effort expended, and there were difficulties in achieving daily targets. Therefore, this study aims to measure the influence of compensation, work motivation, and work discipline on driver performance in Bekasi Regency. The research method used is quantitative with a sample of 70 respondents. Data analysis was conducted using SmartPLS 4.0, with the research results showing that compensation, work motivation, and work discipline significantly influence driver performance. With an R-Square value of 0.807, this means that the variables of compensation, work motivation, and work discipline can explain 80.7% of driver performance.